The landscape of epilepsy surgery in older adults: Challenges and opportunities - Vineet Punia (Epilepsia Open)
Abstract The prevalence of epilepsy increases with age, and with the aging population, the number of drug‐resistant epilepsy (DRE) cases is expected to rise. However, epilepsy surgery remains underutilized and is typically offered to younger adults. Despite historical hesitancy due to concerns over risks and outcomes, evidence over the last two decades shows that epilepsy surgery in older adults (≥50 years) can achieve seizure freedom. Seizure outcomes in older adults are comparable to those in younger adults, with some studies indicating even higher seizure freedom rates in patients over 60. However, concerns persist regarding surgical risks, cognitive decline, and postoperative complications. Older adults undergoing epilepsy surgery have a higher comorbidity burden, which may be associated with lower seizure freedom rates and an increased likelihood of non‐home discharge post‐surgery. Additionally, frailty can influence post‐surgical disposition, although its impact on seizure outcome remains unclear. Surgical complications are more common in older adults, with a higher incidence of language disturbances, infarctions, and subdural hygromas—an issue exclusively observed in this population. Cognitive outcomes remain heterogeneous, with older adults at greater risk of verbal memory decline, particularly after dominant hemisphere resections. However, studies indicate that quality of life improves after surgery, particularly in patients with seizure freedom. Minimally invasive procedures such as laser interstitial thermal therapy (LITT) and neuromodulation techniques like vagus nerve stimulation (VNS) and responsive neurostimulation (RNS) offer promising alternatives for those who are not ideal candidates for resective surgery. Future research will help refine patient selection, address the impact of frailty, and explore long‐term outcomes. Despite the risks, age alone should not preclude epilepsy surgery, and individualized decision‐making remains key to optimizing outcomes. Plain Language Summary In our rapidly aging world, an increasing number of older adults will have drug‐resistant epilepsy. Epilepsy surgery can be a safe and effective option for adults over 50, and in many cases, they do just as well as younger patients in becoming seizure‐free. While there is a slightly higher risk of complications, these risks should be weighed against the potential benefits. Older adults often have other health issues that may affect recovery. Memory and thinking changes can happen, especially with age, but outcomes vary. Age alone should not prevent someone from being considered for surgery. Each case deserves careful, personalized evaluation.